The Failure of Moon Jae In Governmental Policy to Solve the Declining Birth Rate - Aulia Faza Fachna, Faradha; Alexandra, Frisca (Pusat Studi Gender Universitas Jember, 2025)
The declining birth rate in South Korea has become a crucial issue affecting the country’s demographic balance since the early 2000s. This study analyzes the failure of birth rate policies during President Moon Jae In’s administration using Ted Hopf’s constructivism approach, which emphasizes the role of identity, norms, and social constructions in shaping public policies. the result show that despite the implementation of policies such as financial assistance and the recognition of non-traditional families, their effectiveness remains limited. the dominance of social norms emphasizing the importance of marriage before having children, along with changing social values that encourage younger generations to delay marriage, are key factors hindering policy success. therefore, more responsive policies that adapt to social dan cultural shifts are needed to address the declining birth rate more effectively. This study contributes to understanding the relationship between social norms, cultural identity, and social constructions in public policy formulation in South Korea. it also provides insights for policymakers in addressing demographic challenges in the future.